2011
DOI: 10.1038/ijo.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness, central blood pressure and body size in health and disease

Abstract: Background: Body size is associated with increased brachial systolic blood pressure (SBP) and aortic stiffness. The aims of this study were to determine the relationships between central SBP and body size (determined by body mass index (BMI), waist circumference and waist/hip ratio) in health and disease. We also sought to determine if aortic stiffness was correlated with body size, independent of BP. Methods: BMI, brachial BP and estimated central SBP (by SphygmoCor and radial P2) were recorded in controls (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
11
25
0
1
Order By: Relevance
“…In the present study, overall adiposity rather than central adiposity plays a significant role in increasing both bSBP and cSBP. Our results confirm and expand on the findings by Kolade et al 29 who identified a differential association between bSBP and cSBP with WC/hip ratio. It has been postulated 29 that the increased HR, cardiac output and peripheral vasodilatation identified in “healthy” obese subjects 31, 32 may explain the differences between bSBP and cSBP and body size.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, overall adiposity rather than central adiposity plays a significant role in increasing both bSBP and cSBP. Our results confirm and expand on the findings by Kolade et al 29 who identified a differential association between bSBP and cSBP with WC/hip ratio. It has been postulated 29 that the increased HR, cardiac output and peripheral vasodilatation identified in “healthy” obese subjects 31, 32 may explain the differences between bSBP and cSBP and body size.…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm and expand on the findings by Kolade et al 29 who identified a differential association between bSBP and cSBP with WC/hip ratio. It has been postulated 29 that the increased HR, cardiac output and peripheral vasodilatation identified in “healthy” obese subjects 31, 32 may explain the differences between bSBP and cSBP and body size. Our data suggests that cardiac output and peripheral resistance, but not HR, play a role in the differential association between bSBP and cSBP and body size.…”
Section: Discussionsupporting
confidence: 93%
“…This association has also been proved in other studies [23]. Furthermore, the body mass is directly related to the arterial stiffness.…”
Section: Discussionsupporting
confidence: 62%
“…Fasting glucose and BMI in our acromegalic patients were indeed higher than in controls. BMI, impaired glucose tolerance, and diabetes are associated with higher arterial stiffness in the general population (33,34,35), and their role in contributing to increased arterial stiffness in the acromegalic population cannot be completely ruled out. At variance, LDL-C levels were lower in our NOR-ACRO compared with NOR-CTR; a possible contribution of higher lipoprotein(a), found to be associated with acromegaly (36), should be considered.…”
Section: Discussionmentioning
confidence: 99%